Development of the Iguaçu´s Surubim (Steindachneridion sp., Garavello (1991)) (Siluroidei:Pimelodiae) in darkness during the initial phase, fed with different diets - Feiden, Aldi (2005)
The experiment verified the development of Iguaçu´s surubim (Steindachneridion sp.) larvae, submitted to different diets in darkness. 35L-aquariums were used, in a completely randomized design, with five treatments and four repetitions. Each aquarium had 15 larvae with 8,35±0,85 mm and 6,75±0,64 mg, and the treatments were the following diets: Artemia(A); ration(R); zooplankton(Z); Artemia+ration(A+R); and zooplankton+ration (Z+R); After 29 days, the treatments A+R and Z+R was 1036 mg and 859 mg, respectively, significantly higher (P < 0,01), that A and Z, with 536 and 270 mg, respectively. In the treatment R there was no larvae survival, and presented high cannibalism (71%), which was also observed in other treatments, in smaller rates. This results led to the conclusions that the association of live and artificial diets in darkness provided best development, but it does not reduce the cannibalism.